An integrated intersection design for promoting bus and car traffic. (July 2021) - Gu, Weihua; Mei, Yu; Chen, Haoyu; Xuan, Yiguang; Luo, Xiaochun
Highlights: Studied a novel intersection design integrating bus priority measures and pre-signal. Developed coordination plan between pre-signal and main signal for bus signal priority. Estimated expected bus delay and car discharge capacity of the proposed design. The design can reduce bus delays and improve car capacities at busy intersections. The benefits are fairly robust considering real-world operating features. Abstract: Signal priority and exclusive bus lanes are common measures used to promote bus travel at signalized intersections. However, these bus priority measures create significant damage to the car traffic especially at intersections with heavy bus and car traffic. For this reason, bus priority is not welcome at busy intersections. We examine a novel intersection approach design that can solve the above dilemma. The design integrates a bus lane, bus signal priority, and a midblock pre-signal for sorting different car traffic streams in tandem in the approach. Car capacity gains from the use of pre-signal can potentially recover the car capacity lost to bus lane and signal priority schemes. This paper first presents how the pre-signal and main signal can be timed to realize bus signal priority, and where the pre-signal should be placed. Models are then formulated for estimating the expected bus delay and car capacity under the integrated design. They are compared against three alternative designs, including a conventional intersection design without bus priority or pre-signal. Numerical results unveil that the integrated design produces not only significant bus delay savings, but also higher car capacities in most instances. Even greater car capacity gains are observed with higher bus frequencies. Moreover, the benefits are fairly robust when real-world operating features, such as bus arrival time prediction error, are considered. Thus, the integrated design can potentially promote both bus and car traffic at congested intersections.